Diversity assessments of native and alien vascular plants in Gashaka Gumti National Park, northeast Nigeria - Hammanjoda, Salihu Abba; Nulit, Rosimah; Yap, Chee Kong; Nformi, Umaru Buba; Nodza, George Isaac; Saba, Abdulwakil Olawale; Besi, Edward Entalai; Go, Rusea (Phytotaxa, 2025)
Protected Areas play a crucial role in biodiversity conservation and the prevention of biodiversity loss on a global scale. The Gashaka Gumti National Park (GGNP) is Nigeria’s largest and most biodiverse protected area, serving as a habitat for numerous endemic and endangered species. Despite its significance, limited research has been conducted on the park’s flora, and there is no comprehensive record of its vascular plant species. This gap prompted the development of an updated floristic checklist to guide conservation efforts. This study aimed to present a revised checklist of vascular plants in GGNP by synthesizing relevant sources, including field surveys, herbarium specimens, and existing literature from online databases. The findings documented a total of 1 018 plant species belonging to 126 families, with Fabaceae, Orchidaceae, and Rubiaceae being the most dominant. The majority of recorded taxa were trees, with native species constituting 95.2% of the flora. Importantly, the study identified 105 plant species that had not been previously recorded in Nigeria, highlighting the park’s contribution to understanding the botanical diversity of the country. However, the study also revealed a significant threat to the park’s ecosystem from invasive alien species. The conservation status of many taxa in the park remains unassessed according to the IUCN List of Threatened Species, emphasizing the need for further evaluations and conservation strategies. In conclusion, this study underscores the vital role of protected areas in biodiversity conservation and the urgent need for ongoing botanical research and conservation efforts in the region.